Degenerations of $(1,7)$-polarized abelian surfaces - Melliez, F.; Ranestad, K. (MATHEMATICA SCANDINAVICA, 2005)
The moduli space of $(1,7)$-polarized abelian surfaces with a level structure was shown by Manolache and Schreyer to be rational with compactification the variety of powersum presentations of the Klein quartic curve. In this paper the possible degenerations of the abelian surfaces corresponding to degenerations of powersum presentations are classified.